Keberadaan Kontainer sebagai Faktor Risiko Penularan Demam Berdarah Dengue di Kota Palu, Sulawesi Tengah - Junus Widjaja (Loka Litbang Kesehatan Pangandaran, 2011)
Abstract. During the period of three years (2003-2005) the number of dengue cases in Palucontinues to increase, the number of cases in 2003 with 173 people with death ot 10 people(CFR 5.78%), in 2004 the number of cases found among 210 people died (CFR 4.32%) and2005 the number of cases found 627 people with 12 deaths (CFR2.21%). Objectives knowthe type, material and location conteiner as risk factors for the occurence of dengue in thecity of Palu. The presence of mosquito breeding sites by speceis kontainer buckets(OR=3.6p=0.00) and jars (OR=5.2 p=0.03), plastic materials (OR=1.7 p=0.01), state conteiner notclosed (OR=0.04 p=1.2 and location conteiner in the house (OR=1.3 p= 0.01) were riskfactors associated with the incidence of dengue in the city of Palu. Need extension 3 M, anincrease in the real role of DHF and soon formed a working group JUMANTIK in Palu